Estudio de la Calidad de Agua del Río San Pedro, ubicado dentro del Distrito Metropolitano de Quito en el periodo 2013-2019. - Pilalumbo Armas, Jonathan Javier (2020)
This research work, a study of the water quality of the San Pedro River, located within the Metropolitan District of Quito, was carried out since 2013 to 2019 Period, with the application of the Simplified Water Quality Index (ISQA). On the other hand, it was proposed to determine the water quality of the San Pedro River with the time series decomposition method, in order to plan a projection of the water quality to four future years, from 2020 to 2024. The current situation of the wastewater generated in the Metropolitan District of Quito has reached worrying levels of pollution in the sewage collection system that ends in natural flows without prior treatment. In the last decade, the quantity and quality of water resources have decreased significantly, and surface water conditions are expected to deteriorate in the medium and long term. This situation has configured an important environmental problem in the entire stretch in Quito city, because domestic, industrial and agricultural discharges, without prior treatment, constitute the main sources of water pollution and public health. In this context, the San Pedro River has become a receptor for domestic waste and effluent. The described circumstances justified the importance of applying the mathematical model that allowed simulating the behavior of water quality in a natural stream, describing the ecological state of a river system and predicting future situations when certain initial or limit conditions are altered. The results of the physicochemical parameters were analyzed in the database of the National Secretary of the Environment of the Metropolitan District of Quito, from the period 2013-2019, where it is detailed that the Temperature (T) varied from 17.6 ° C at 13 ° C, Chemical Oxygen Demand (COD) ranged from 8mg / L to 80mg / L, Total Suspended Solids (TSS) from 13mg/ Lt 126mg / L-1, dissolved oxygen (DO) from 8.76mg / L to - 6.23 mg / L-1 and the electrical conductivity (EC) between 742uS / cm-1 to 466 uS / cm. For this reason, the index values points out the water quality for the years: 2013 it is 58.9; in 2016 of 59.7; in 2018 it was 54.9 and in 2019 it was 51.5, in the San Pedro River. Similar results were obtained in the forecast, of the ISQA values in the year 2021 is 51.1; in the year 2022 it is 51.4; for the year 2023 it is 51.9; It is found that in all the years from 2020 to 2023 the water quality is regular because it is in the value of 50-70, and it is concluded that the water is suitable with purification treatment for human consumption, equivalently for irrigation and the industry.